Synthetic aperture sonar as a tool for rapid high resolution deposit estimation - Alden Ross Denny; Rolf Birger Pedersen (Society for Mining, Metallurgy & Exploration, 2014)
"Synthetic Aperature Sonar (SAS) is a powerful tool for ultra-high resolution marine survey. The Kongsberg HiSAS system deployed on the HUGIN AUV has a rangeindependent resolution of 3x3 cm for sonar image and ~10x10cm for the interferometric bathymetry product [1]. This resolution is achievable for areas up to 50 km2 on a single survey mission providing huge multi-attribute datasets. This technology, originally designed for military and oil-industry applications, has the potential to revolutionize scientific seafloor mapping. The extreme resolution of this technique allows for deposit mapping in and around seafloor hydrothermal systems, including the discovery of extinct venting structures. By clearly distinguishing between volcanic and hydrothermal landscapes based on features below the resolution of conventional multibeam systems, SAS enables an entirely new level of hydrothermal deposit survey. Additionally due to the extreme resolution of this survey technology, repeat survey and change detection should allow centimeter-scale changes in deposit morphology to be routinely detected over an entire hydrothermally venting region. In collaboration with the EU funded MIDAS project, the Centre for Geobiology at the University of Bergen will deploy the HUGIN AUV this summer at two distinct shallow venting systems on the Arctic Mid-Ocean Ridge system. The AUV will collect repeat bathymetry at the Jan Mayen Vent Field, and extend the SAS coverage to include newly discovered venting sites. We will present the preliminary findings of this expedition, including the first deposit estimations made from full-resolution SAS mosaics."